Interactive Learning Media Development using Articulate Storyline in Fundamentals of Electric Power Engineering - Abelriadne Gentarefori Samala; Taali Taali; Oriza Candra; Irma Husnaini (Jurnal Teknologi Informasi dan Pendidikan, 2022)
Interactive learning media is a teaching material that is needed as intermediary information that can directly interact with students so it can be easily learned independently. This research aims to produce a valid and practical interactive learning media on the subject of Basic Electrical Engineering using Articulate Storyline at SMK Negeri 2 Lubuk Basung. The type of research used is R&D (Research & Development) with a 4-D development model that goes through four main procedures: (1) Define, (2) Design, (3) Development, and (4) Disseminate. Media experts tested this learning media, subject matter experts, teachers, and students at SMK Negeri 2 Lubuk Basung. The results of the media expert assessment were 0.89 (valid), the subject matter expert 0.87 (valid), the practicality test by teachers 91% (very practical), and the practicality test by students of SMKN 2 Lubuk Basung obtained 91% (very practical). Based on the assessment results, it shows that the interactive learning media with a clear storyline on the basic electrical engineering topics is very good and practical to use in learning activities at SMK (Vocational High School).